Ventilation Control Measures Taken And Interpretation Of Chromatograph Analyses During Recent Arizona Mine Fires - Ralph K. Foster (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1982)
During five underground mine fires which occurred in Arizona during 1980 and 1981, sealing the fire area became necessary. To minimize leakage into the fire area, ventilation control measures were instituted to balance pressure across the bulkheads. Problems en- countered in sealing the fire areas and measures taken to improve these conditions are discussed. The routing of the ventilation and ventilation control to en- sure the workers' safety were also important considerations in reopening the mines. The use of continuous CO monitors is discussed. One important consideration was the condition of the fire, and chromatographic analysis was used to establish this. Graphs comparing the Trickett ratio, carbon monoxide, carbon dioxide, and oxygen concentrations are given. The Trickett ratio was useful but needed to be augmented by the comparison of CO, C02, and 02. Problems with getting good samples from sealed areas and recommended procedures that were developed during these fires are discussed.